2017
DOI: 10.7717/peerj.3908
|View full text |Cite
|
Sign up to set email alerts
|

Neurodynamic mobilization and foam rolling improved delayed-onset muscle soreness in a healthy adult population: a randomized controlled clinical trial

Abstract: ObjectivesCompare the immediate effects of a Neurodynamic Mobilization (NM) treatment or foam roller (FR) treatment after DOMS.DesignDouble blind randomised clinical trial.SettingThe participants performed 100 drop jumps (5 sets of 20 repetitions, separated by 2 min rests) from a 0.5-m high box in a University biomechanics laboratory to induce muscle soreness. The participants were randomly assigned in a counter-balanced fashion to either a FR or NM treatment group.ParticipantsThirty-two healthy subjects (21 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 40 publications
(63 reference statements)
3
28
0
7
Order By: Relevance
“…Researchers also used Borg scales or numerical ratings scale as means to collect perceived recovery ( Healey et al, 2014 ; Peacock et al, 2015 ; Fleckenstein et al, 2017 ; Kalén et al, 2017 ; Rey et al, 2017 ; Beier et al, 2019 ; Table 4 ). Considering that pain is not objectively measurable, these different scales offer a simple solution to assess the quality and speed of recovery of DOMS ( Jay et al, 2014 ; MacDonald et al, 2014 ; Romero-Moraleda et al, 2017 , 2019 ; Naderi et al, 2019 ; Table 5 ). The algometer is also used to measure the PPT reliably, both at the muscular and joint levels, after FR routine.…”
Section: Foam Rollingmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also used Borg scales or numerical ratings scale as means to collect perceived recovery ( Healey et al, 2014 ; Peacock et al, 2015 ; Fleckenstein et al, 2017 ; Kalén et al, 2017 ; Rey et al, 2017 ; Beier et al, 2019 ; Table 4 ). Considering that pain is not objectively measurable, these different scales offer a simple solution to assess the quality and speed of recovery of DOMS ( Jay et al, 2014 ; MacDonald et al, 2014 ; Romero-Moraleda et al, 2017 , 2019 ; Naderi et al, 2019 ; Table 5 ). The algometer is also used to measure the PPT reliably, both at the muscular and joint levels, after FR routine.…”
Section: Foam Rollingmentioning
confidence: 99%
“…To this end, researchers used surface electromyography (EMGs) to appreciate whether muscle activation increase was associated with better performance, and further reduced the risk of injury ( Macgregor et al, 2018 ). EMGs were recorded non-invasively by positioning electrodes directly on a shaved skin cleaned with alcohol ( Ginszt et al, 2017 ; Romero-Moraleda et al, 2017 ; Hodgson et al, 2018 ; Madoni et al, 2018 ; Beier et al, 2019 ; Capobianco et al, 2019 ; Kim et al, 2019 ; Mazzei, 2019 ; Ye et al, 2019 ; Table 7 ). Recently, the development of tensiomyography allowed rapid and reliable non-invasive investigations of the contractile properties of the skeletal muscle ( Martínez-Cabrera and Núñez-Sánchez, 2016 ; Murray et al, 2016 ; Schroeder et al, 2017 ; Macgregor et al, 2018 ; Table 7 ).…”
Section: Foam Rollingmentioning
confidence: 99%
“…In particular, several studies have investigated the effects of FR following exercise in the lower limbs (MacDonald et al, 2013; Behara and Jacobson, 2017; Cavanaugh et al, 2017a) with authors reporting improvements in either ROM, jump height, power, sprint performance, or change of direction (MacDonald et al, 2014; Cheatham et al, 2015; Pearcey et al, 2015; Schroeder and Best, 2015; Freiwald et al, 2016; D’Amico and Gillis, 2017; Rey et al, 2017; Richman et al, 2018). Recent evidence has also suggested that FR may benefit functional outcomes during the recovery period (Fleckenstein et al, 2017) despite no changes in tissue properties (Schroeder et al, 2018); however, specific ECC exercise studies are limited (Pearcey et al, 2015; Romero-Moraleda et al, 2017). Additionally, it is unclear if neurophysiological mechanisms (i.e., VA or PTT) contribute to the performance improvements (i.e., jump performance) often observed following FR.…”
Section: Introductionmentioning
confidence: 99%
“…Romero-Moraleda et al divided the subjects with delayed-onset muscle soreness into the nerve mobilization group and the foam roller group to compare pain, rectus femoris muscle strength, and muscle activity, and both groups were found to have reduced pain. 22 However, only the foam roller group showed an increase in muscle strength and activity of the rectus femoris. In healthy people, a change in grip strength was observed by applying nerve mobilization and general stretching, and there was no significant change between the two groups.…”
Section: Journal Of Musculoskeletal Science and Technologymentioning
confidence: 91%